Evaluation of aquatic insects as bioindicators of water quality in industrial areas of Surabaya, East Java - Maximilliana Taek, Gemma Galgani (Generasi Biologi Indonesia, 2024)
In the industrial area of Surabaya, water quality monitoring is crucial for maintaining environmental sustainability and human health. Aquatic insects have been identified as effective bioindicators for assessing water quality in this context. This article aims to explore the biological characteristics of aquatic insects, their role as bioindicators, and their relationship with water quality parameters near the industrial area of Surabaya. Through a literature review approach, relevant sources were analyzed to obtain comprehensive insights. The biological characteristics of aquatic insects, such as abundance, species diversity, tolerance to pollution, and life cycle and reproduction, enable them to provide indications of pollution levels and the industrial impact on aquatic ecosystems. Pollution[1]sensitive aquatic insects, including certain species of Ephemeroptera, Plecoptera, and Trichoptera (EPT), tend to decline in abundance and diversity when water quality deteriorates. Conversely, the dominance of pollution-tolerant species, such as Chironomidae (non-biting midges), may indicate the impact of industrial pollution on water quality. Additionally, disruptions to the life cycle and reproduction of aquatic insects can signal water quality issues near Surabaya’s industrial zone. A decrease in reproduction or delayed growth in aquatic insects may indicate the presence of toxic substances or unsuitable environmental conditions. Water quality monitoring should not solely rely on aquatic insect bioindicators. Other parameters, such as pH, dissolved oxygen, turbidity, and chemical indicators, are essential for a more comprehensive analysis.